Page 7 - Bahan Ajar Bismillah(2)
P. 7

c.         =    + 9
                                 3
                               +      =  (   +   ) + 9
                                               3
                                    =     + 3     +3     +    + 9
                                                       2
                                         3
                                                             3
                                               2

                           ′(  )  =           + h  −   (  )
                                    lim
                                    h→0         h
                                          3
                                                2
                                                         2
                                =          + 3     +3     +    + 9 − (   + 9)
                                                                        3
                                                              3
                                    lim
                                    h→0                    h
                                                   2
                                           2
                                =       3     +3     +    3
                                    lim
                                    h→0         h
                                             2
                                                          2
                                =         (3   + 3     +    )
                                    lim
                                    h→0          h
                                                        2
                                            2
                                =  lim(3   + 3     +    )
                                    h→0
                                       2
                                                    2
                                =  3   + 3  . 0 + 0
                                =  3   + 0 + 0
                                       2
                                       2
                                =  3  

                                3
                     d.         =
                                  
                               +      =    3
                                            +   


                           ′(  )  =           + h  −   (  )
                                    lim
                                    h→0         h
                                =        3  −  3
                                    lim    +      
                                    h→0    h
                                =        3  −3(  +  )
                                            (  +  )
                                    lim
                                    h→0     h
                                =       3   − 3   − 3  
                                    lim
                                    h→0   hx(x + h)

                                =          −3  
                                    lim
                                    h→0 hx(x + h)



               3 | P a g e                                                                   K E L A S   X I
   2   3   4   5   6   7   8   9   10   11   12